Does Firing a CEO Pay Off?. Issue 1 (13th July 2018) - Alexandridis, George; Doukas, John A.; Mavis, Christos P.
Abstract: We examine whether involuntary chief executive officer (CEO) replacements pay off by improving firm prospects. We find CEO successors' acquisition investments to be associated with significantly higher shareholder gains relative to their predecessors and the average CEO. This improvement in postturnover acquisition performance appears to be a function of board independence, hedge fund ownership, and the new CEO's relative experience. CEO successors also create sizable shareholder value by reversing prior investments through asset disposals and discontinuing operations and by employing more efficient investment strategies. Our evidence suggests that firing a CEO pays off.